Tuberculosis: Case Finding in Public Health Center of Blora, Indonesia - ahmad musyafa (Berita Kedokteran Masyarakat (BKM), 2017)
Background: Tuberculosis is a disease of international concern. Control measure have been implemented in the World and Indonesia. One of the indicators of TB prevention program in Indonesia is Case Notification Rate (CNR), through case finding to screen of suspected TB, physical examination, laboratory and diagnosis Objective: Implementation of TB case finding program in Blora Distric, Indonesia, 2017 Methods: A descriptive observational study of evaluation. Subjects were 12 TB programmers at Public Health Center, 12 laboratory workers and 1 supervisor of Blora District Health Office. Data were collected by in-depth interviews and observations on input, process, output and outcome aspects. Results: Input aspect, 75% of respondents have double job, with duration of >5 years (75%) and was followed TB training >5 years (66%). Aspects of process, planning, budget requirements, targeting above 90%. Increase internal lineage (58%). Implementation already uses active search (92%) and passive (67%). Involvement of health cadres is not optimal, people are more confident to health workers in the village. PPM has not gone well (17%) so many patients are not reported in PHC. Clinics, hospitals and private practice doctors have not yet applied DOTS strategy treatment. Monitoring and evaluation has been done by wasor >2 times/year 33% and <2 times/year 67%. The CNR output aspect of 2016 128/100.000 population is below the national target of 316/100.000 population. Outcome aspect consists of 91.1% cure rate and 3.5% death. Conclusions: Overall TB case finding in Blora has gone well. But there are still shortcomings in the input aspect, needs to improve the skills of TB programmers with training and refresher.  On process aspect is still necessary increasing PPM by involving the private sector, hospitals and polyclinics, involving the village midwife actively encompassing TB cases cross program and sector network. So it can increase the CNR TB in Blora.